Ultrasonic Extraction of Nothaphoebe Coriacea Bark and Its Antioxidant Evaluation - Putri, Salsabila Aqila; Febrianti, Ratih; Nisa, Khoirun; Sunardi, Sunardi (SCIENCE AND TECHNOLOGY FACULTY OF UNIVERSITAS ISLAM NEGERI RADEN FATAH PALEMBANG, 2020)
Nothaphoebe coriacea (in Kalimantan, Indonesia, commonly known as gemor) is a native wetland-plants that can grow well in swampy areas. This tree is distributed throughout South and Central Kalimantan, Indonesia. The bark of Nothaphoebe coriacea is used for bioactive compound source for larvacide, mosquito repellent, hio and glue. The objective of this research was to investigate the ultrasound-assisted extraction methods for the extraction of antioxidants compounds of Nothaphoebe coriacea. The barks were subjected to ultrasound‐assisted ethanolic and hexane extraction followed by fractionation (using ethyl acetate, chloroform, and hexane) and the antioxidant activity test was performed. The activity of antioxidant was carried out through a DPPH method. The highest antioxidant activities are shown in ethanol extract with IC50 value of 72.36 μg/mL and chloroform fraction of ethanol extract with IC50 value of 54.18 μg/mL.